Challenges and Barriers in Public Services Innovations in Malaysia - Nor Ashikin Mohamed Yusof; Salwa Ahmad Rafee; Aspah Aini Ishak; Muhammad Rohaizad Razali; Intan Sazrina Saimy (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2022)
For the last two decades, the government of Malaysia has been moving away from the traditional roles of managing, governing and providing services for the country. The government is actively encouraging the public or civil servants to join the bandwagon and create innovations in the course of their works, protect their innovations with intellectual property protection and whenever possible commercialize them. Such a giant leap is in line with the provisions of Science, Technology and Innovation Policy 2020 in the efforts of converting Malaysian’s economy from manufacturing-based to knowledge and innovation-based instead. It also provides is a good opportunity for the government to create a new source of financial and economic income, save resources and increase the intellectual property index and ranking globally. A lot of incentives, resources and supports were re-channeled for that purpose. To date, the implementation, real outcomes, outputs and impacts of the government’s servant in the innovative activities remain largely unmeasured. Whether the return of investment for such undertakings is commensurate with the efforts or otherwise. What happens to the “innovators” and their inventions are untraced. This paper presents part findings on Malaysian’s experiences towards creating innovations and fulfilling the STI Policy’s objectives. The article focuses on the civil servants’ involvement in developing or creating innovative products or services and their challenges in materializing that policy objective. The study was conducted amongst public servants. Primary data was collected through interviews and focus group discussions with the winning organizations or units of the National Award for Public Sector Innovations. In total, 86 participants from four winning organizations were involved. The civil servants’ efforts are commendable and encouraging. This shows the objectives of the STI Policy are correct. Secondly, the strategies of the STI Policy are only workable if they are supported with a correct support system and well-designed implementation plan or programs, The result also shows that the STI Policy document is broad-ranging, inclusive and unlimited for private sectors, big companies or intended for machines, engineering or hardware only. It includes public sector as well as “soft” innovations in terms of service and management processes, produced by the civil servants are equally valuable, useful and should not be disregarded. However, the government must iron out few challenges in ensuring the innovation program for civil servants are sustainable. The findings of this paper are useful as policy input in improving the support systems, designing action plans or policy interventions for STI Policy in the future. Keywords: public sector innovation, service innovation, National Science Technology and Innovation Policy 2013-2020